Simulation of a Hydrogen-Air Diffusion Flame under Consideration of Component-Specific Diffusivities - Barabas, Jana; Jovicic, Vojislav; Delgado, Antonio (Applied Sciences, 2022)
This work deals with the numerical investigation of a three-dimensional, laminar hydrogen-air diffusion flame in which a cylindrical fuel jet is surrounded by in-flowing air. To calculate the distribution of gas molecules, the model solves the species conservation equation for N-1 components, using infinity fast chemistry and irreversible chemical reaction. The consideration of the component-specific diffusion has a strong influence on the position of the high-temperature zone as well as on the concentration distribution of the individual gas molecules. The calculations of the developed model predict the radial and axial species and temperature distribution in the combustion chamber comparable to those from previous publications. Deviations due to a changed burner geometry and air supply narrow the flame structure by up to 50% and the high-temperature zones merge toward the central axis. Due to the reduced inflow velocity of the hydrogen, the high-temperature zones develop closer to the nozzle inlet of the combustion chamber. As the power increases, the length of the cold hydrogen jet increases. Furthermore, the results show that the axial profiles of temperature and mass fractions scale quantitatively with the power input by the fuel.
CRIS-Team Scopus Importer:2022-04-08
Keywords: flame structure; hydrogen combustion; multi-component diffusion; numerical simulation; OpenFOAM